MEDIA PAPAN KAIN FLANEL UNTUK MENCEGAH KEBOSANAN SISWA DALAM PROSES PEMBELAJARAN UNTUK MENDUKUNG PROGRAM GO GREEN DI SD NEGERI SEMANTEN - Muhammadin AL Fath, Ayatullah (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2022)
The purpose of this study is to describe the flannel board media by replacing learning books to prevent student boredom and reduce the use of plastic and is environmentally friendly. The method used is a qualitative approach with a descriptive type. Data collection techniques using interviews, observation, and documentation. Interviews were addressed to fifth-grade teachers, students, and guardians. Observations were made to determine the implementation of social studies learning at SD Negeri Semanten class V. The findings before the application of flannel board media students lacked focus on learning and felt bored, causing less efficient learning. After the application of flannel board media, student boredom can be reduced and student activity can be seen in the learning process. For learning that supports the go green program, namely by replacing the media material from plywood, it is replaced with cork, besides that students' creativity is also seen and the flannel board learning media can be used as alternative learning in class V theme 4, sub-theme 1.